Effectiveness of CT Scan Thorax Parameters in Diagnosing Pulmonary Tuberculosis at the Radiology Department of Siti Rahmah Islamic Hospital Padang - Nansih, Livia Ade; Yudha, Sagita; Rosfadelli, Tahnia (Oshada, 2026)
A chest CT scan is an imaging modality used for early detection of suspected abnormalities in the thoracic region, complementing conventional chest radiography. CT produces cross-sectional images that support pathological investigation and evaluation of previous diagnoses. Standard chest CT protocols generally cover the area from the lung apex to the costophrenic sinuses, with a slice thickness of 2.5 mm, soft tissue window width of 350 and level of 50, and lung window width of 1500 and level of -700. However, at the Radiology Department of RSI Siti Rahmah Padang, the scan area extends from the 5th cervical vertebra (C5) to 2 inches (5 cm) inferior to the xiphoid process, using a slice thickness of 5–10 mm. The mediastinum window is set at width 400 and level 40, while the lung window ranges from width 1500–1800 and level -200 to -300. This study aimed to determine the effectiveness of these CT parameters in the clinical management of pulmonary tuberculosis (TB). Conducted in June 2025, the research used a descriptive qualitative design with two radiology specialists as informants. Data were collected through literature review, observation, interviews, and documentation, and analyzed comparatively by aligning field findings with theoretical references through data reduction, presentation, and conclusion drawing. Results showed that the scan range from C5 to 5 cm below the xiphoid process provides adequate thoracic visualization in pulmonary TB cases, ensuring full depiction of the apical region and lung parenchyma, although extension to the suprarenal area is recommended. A 5 mm slice thickness effectively supports multiplanar reconstruction and lesion distribution analysis. The mediastinum and lung window settings enhance visualization of fibrotic areas and parenchymal abnormalities, confirming the effectiveness of these parameters in diagnosing pulmonary TB.